QUALITY OF FINANCIAL REPORTS THROUGH ORGANIZATIONAL COMMITMENTS AS INTERVENING VARIABLES - Silvia Sari; Berta Agus Petra; Lusiana Lusiana; M Fikri As Falah (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Background : This study aims to examine the effect of the application of regional financial accounting and HR competence on the quality of financial reports with organizational commitment as an intervening variable at the Regional Financial and Asset Management Agency of Sawahlunto City. Method : Methods of collecting data through surveys and questionnaires. The analytical method used is Multiple Linear Regression Analysis with SPSS IBM 25. By distributing questionnaires to 80 respondents. Result : The results of data analysis concluded, partially (t test) obtained: (a) there is a positive and significant effect between the application of regional financial accounting on organizational commitment. Conclusion : (b) there is a negative and significant influence between HR Competence on Organizational Commitment. (c) there is a negative and significant effect between the Application of Regional Financial Accounting on the Quality of Financial Reports. (d) there is a positive and significant influence between HR Competence on the Quality of Financial Statements (e) there is a positive and significant influence between Organizational Commitment on the Quality of Financial Statements. (f) The application of Regional Financial Accounting does not mediate Organizational Commitment to the Quality of Financial Reports. (g) HR competence can mediate Organizational Commitment to the Quality of Financial Reports